PERAN TIK-TOK SEBAGAI SARANA PERKEMBANGAN KOSAKATA DALAM PEMBELAJARAN BAHASA INDONESIA - Aisyah Amini; Febry Amelia; Nurlisa Nurlisa (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2026)
This study examines the role of TikTok as a medium for vocabulary development in Indonesian language learning using a descriptive qualitative literature review approach. The problem underlying this study is the limited vocabulary mastery of students due to the dominance of conventional learning practices and the lack of integration of digital media that align with students’ daily experiences. Data were obtained through an analysis of scientific journals, books, and scholarly articles related to Indonesian language learning, vocabulary acquisition, and the use of social media in education. The findings indicate that TikTok has strong potential as an innovative learning medium because of its audiovisual, interactive, and contextual characteristics. The use of TikTok can increase students’ learning motivation, expand receptive and productive vocabulary mastery, and help learners understand various types of vocabulary, including standard, non-standard, technical, and contextual vocabulary through concise and engaging educational content. In addition, TikTok encourages incidental learning, allowing students to acquire new vocabulary naturally through repeated exposure in authentic contexts. Overall, this study contributes to Indonesian language education by highlighting the effective use of social media in response to the demands of the digital era.